A transparent, conducting tape for flexible electronics - Huang, Ya; Liao, Suiyang; Ren, Jie; Khalid, Bilal; Peng, Hailin; Wu, Hui (Nano research, 2016)
Transparent electrodes are essential components for optoelectronic devices such as displays and thin-film solar cells. Traditionally, the deposition of transparent conducting layers and the sealing of the device are separate steps. Here we report on a highly transparent, conductive, and flexible ＂tape＂, which can be obtained by transferring silver nanowire networks to conventional transparent tape. We utilized the viscidity of the tape to reduce the junction resistance between silver nanowires and further protect the nanowires from corrosion, oxidation and mechanical damage. By this simple method, we obtained a flexible tape with high transparency （-90% at 550 nm wavelength） and low sheet resistance （approaching 22 Ω.sq^-1）. The transparent tape can be attached and stuck firmly on complex surfaces, making the surface highly conductive. We demonstrated the use of the tape as both a conducting layer and a sealing layer for flexible electronics applications including in-situ temperature monitoring and electrochromic devices.